Exploring Communication and Sharing Between Extended Families - Tee, Kimberly; Brush, A.J.; Inkpen, Kori (International Journal of Human-Computer Studies, Special Issue on the family and communication technologies, 2009)
In recent years, computer and Internet technologies have broadened the ways that people can stay in touch. Through interviews with parents and grandparents, we examined how people use existing technologies to communicate and share with their extended family. While most of our participants expressed a desire for more communication and sharing with their extended family, many felt that an increase would realistically be difficult to achieve due to challenges such as busy schedules or extended family members’ lack of technology use. Our results also highlight the complexity of factors that researchers and designers must understand when attempting to design technology to support and enhance relationships, including trade-offs between facilitating interaction while minimizing new obligations, reducing effort without trivializing communication, and balancing awareness with privacy.
http://dx.doi.org/10.1016/j.ijhcs.2008.09.007